2022
DOI: 10.3390/molecules27144666
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Inhibits Epstein–Barr Virus Lytic Reactivation in EBV-Positive Cancer Cell Lines through the Modulation of Epigenetic-Related Proteins

Abstract: Reactivation of Epstein–Barr virus (EBV) is associated with EBV-associated malignancies and is considered to be a benefit target for treatment. Andrographolide is claimed to have antiviral and anti-tumor activities. Therefore, this study aimed to investigate the effect of andrographolide on the inhibition of EBV lytic reactivation in EBV-positive cancer cells. The cytotoxicity of andrographolide was firstly evaluated in EBV-positive cancer cells; P3HR1, AGS-EBV and HONE1-EBV cells, using an MTT assay. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Andrographolide inhibits EBV replication by inhibiting the expression of EBV lytic proteins, including Rta, Zta, and EA-D, during lytic activation in P3HR1 cells and thus inhibits the promoter activities of Zta and Rta [27]. Similarly, our previous study also demonstrated that andrographolide inhibits lytic gene expression and hinders the production of viral particles [28,29]. However, the underlying molecular mechanism through which andrographolide performs these functions in each type of epithelial malignancy is still unknown.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Andrographolide inhibits EBV replication by inhibiting the expression of EBV lytic proteins, including Rta, Zta, and EA-D, during lytic activation in P3HR1 cells and thus inhibits the promoter activities of Zta and Rta [27]. Similarly, our previous study also demonstrated that andrographolide inhibits lytic gene expression and hinders the production of viral particles [28,29]. However, the underlying molecular mechanism through which andrographolide performs these functions in each type of epithelial malignancy is still unknown.…”
Section: Introductionmentioning
confidence: 93%
“…Our previous study demonstrated that andrographolide inhibits EBV lytic reactivation through the suppression of lytic protein expression and the inhibition of EBV virion production [28,29]. In this study, we further examined the inhibitory effect of andrographolide on the inhibition of EBV lytic reactivation in HNC cell lines via the treatment of EBV-positive HNC cell lines (HONE1-EBV, SCC25-EBV, and HSC1-EBV) with NaB alone, andrographolide alone, or andrographolide combined with NaB.…”
Section: Andrographolide Inhibits Ebv Lytic Reactivation In Hnc Cell ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AGL greatly inhibited the 3Cpro's interferon (IFN) antagonistic effect by inhibiting the expression of interferon-stimulating genes (ISGs) [185]. AGL prevents EBV reactivation in EBV-positive cancer cells by suppressing EBV lytic genes, most likely via histone modifications such as H3-K9 modification and H3-K27 methylation [186]. AGL has been shown to prevent infections of DENV [184], ZIKV, and other arboviruses [187].…”
Section: Andrographolidementioning
confidence: 99%
“…Inhibits virus replications such HIV, HSV-1, HBV, HCV, ZIKV, DENV, CHIKV, FMDV, and IAV [181,182,184]. Prevents EBV reactivation by suppressing EBV lytic genes via histone modifications [186]. Also prevents IVA-induced inflammation through modulation of NF-κB and JAK-STAT signaling pathways [189].…”
Section: Apigeninmentioning
confidence: 99%